1992
DOI: 10.1212/wnl.42.2.320
|View full text |Cite
|
Sign up to set email alerts
|

Diminished curiosity in patients with probable Alzheimer's disease as measured by exploratory eye movements

Abstract: Clinical accounts of Alzheimer's disease (AD) suggest that some patients exhibit markedly diminished curiosity and initiative early in the course of their illness. Such behavioral changes are extremely difficult to measure experimentally. We studied one aspect of curiosity by measuring exploratory eye movements in response to provocative visual stimuli in 12 patients with probable AD and 10 matched controls. Subjects viewed slides, each of which contained an incongruous or irregular figure paired with a congru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
96
2
6

Year Published

1994
1994
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 130 publications
(115 citation statements)
references
References 0 publications
9
96
2
6
Order By: Relevance
“…The findings are in contrast to our previous report in which PRAD patients were impaired in modulating visual exploration according to variations in the novelty and complexity of emotionally-neutral stimuli using a task design similar to the one in the present study [4]. This dissociation probably reflects differences in the pathological vulnerability of the neural networks that subserve novelty-seeking behaviors versus those that subserve orientation to arousing stimuli.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…The findings are in contrast to our previous report in which PRAD patients were impaired in modulating visual exploration according to variations in the novelty and complexity of emotionally-neutral stimuli using a task design similar to the one in the present study [4]. This dissociation probably reflects differences in the pathological vulnerability of the neural networks that subserve novelty-seeking behaviors versus those that subserve orientation to arousing stimuli.…”
Section: Discussioncontrasting
confidence: 99%
“…As discussed above, they fail to show a preferential viewing of novel events [4]. Furthermore, they have difficulty covertly shifting attention to targets at different spatial locations, especially in the presence of distracters or when attention has first been cued to a location that is different from the one at which the target actually appears [23].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, whereas AD patients show an attentional-shifting deficit in both tasks, PD patients show a deficit in the maintenance of attention across trials in both tasks (see Filoteo et al, 1995 for a review). This consistency also mirrors the disparate pathologies and neurochemical deficits characterizing PD and AD.Finally, the deficit in covert attention shifting in AD patients is also reflected in deficits in overt shifts of attention (Daffner, Scinto, Weintraub, & Mesulam, 1992;Rosler et al, 2000;Scinto, Daffner, Castro, & Mesulam, 1994 (2000) found reduced right parietal activation in AD patients, consistent with the PET and SPECT; findings of right parietal hypometabolism associated with covert attention (Buck et al, 1997;Parasuraman et al, 1992). Individuals with AD are also impaired in making antisaccades; that is, eye movements in a direction opposite to that of a peripheral stimulus with sudden onset (Fletcher & Sharpe, 1988).…”
supporting
confidence: 55%